Third-generation sequencing reveals the spatial variation of microbial composition of airborne bacteria in an intensive dairy farm - Zhang, Qianqian; Ding, Luyu; Xie, Xueying; Ru, Lin; Li, Qifeng; Yao, Chunxia; Solkner, Johann; Jiang, Ruixiang (Frontiers in Microbiology, 2025)
IntroductionThe intensification of livestock farming has led to increased bacterial bioaerosol emissions, posing potential health risks to both animals and humans. This study aimed to investigate the bacterial community composition, abundance, diversity, and variation in different functional zones of cattle farms to assess their impact on public health and environmental quality.MethodsWe employed third-generation sequencing on the PacBio platform to analyze 16S ribosomal RNA (rRNA) sequences from air samples, identifying a diverse range of bacterial phyla, including Proteobacteria, Firmicutes, Verrucomicrobia, Bacteroidetes, Fusobacteria, Actinobacteria, Deinococcus-Thermus, Cyanobacteria, and Acidobacteria. The phylogenetic tree was built using the microbiome abundance of these samples.ResultsNotably, Firmicutes and Proteobacteria were predominantly enriched in the samples, with genera such as Staphylococcus, Acinetobacter, Enterococcus, and Bacillus, and the family Enterobacteriaceae, which was unknown, being particularly abundant. These bacteria are known to be associated with various infections and chronic diseases. Correlation and canonical correspondence analysis (CCA) revealed that environmental factors, particularly ultraviolet (UV) radiation and global horizontal irradiance (GHI), significantly influence microbial species distribution, with R2 values of 0.774 (p < 0.05) and 0.769 (p < 0.05), respectively. We further calculated the alpha and beta diversity of microbiome in these samples and observed that fermenting manure (F1), fresh manure (X2), and piled-up manure after fermentation (D3) samples have the highest alpha diversity, while PC1 from beta diversity, that is, weighted principal coordinates analysis (PCoA), explained 32.66% of the variance in the data. Interestingly, the relative abundance of the Kocuria genus was significantly different between the waste management area (FW) and the milking parlor (NT) (t-test, p < 0.013).DiscussionOur findings underscore the importance of understanding the complex microbial ecosystems in livestock farming environments and highlight the need for targeted interventions to mitigate public health risks associated with bacterial bioaerosols.